Advantages of N-Type Hydrogenated Microcrystalline Silicon Oxide Films for Micromorph Silicon Solar Cells - Amornrat Limmanee; Songkiate Kittisontirak; Sorapong Inthisang; Taweewat Krajangsang; Jaran Sritharathikhun; Kobsak Sriprapha (International Journal of Photoenergy)
We report on the development and application of n-type hydrogenated microcrystalline silicon oxide films (n μc-SiO:H) in hydrogenated amorphous silicon oxide/hydrogenated microcrystalline silicon (a-SiO:H/μc-Si:H) micromorph solar cells. The n μc-SiO:H films with high optical bandgap and low refractive index could be obtained when a ratio of carbon dioxide (CO2) to silane (SiH4) flow rate was raised; however, a trade-off against electrical property was observed. We applied the n μc-SiO:H films in the top a-SiO:H cell and investigated the changes in cell performance with respect to the electrical and optical properties of the films. It was found that all photovoltaic parameters of the micromorph silicon solar cells using the n top μc-SiO:H layer enhanced with increasing the CO2/SiH4 ratio up to 0.23, where the highest initial cell efficiency of 10.7% was achieved. The enhancement of the open circuit voltage (Voc) was likely to be due to a reduction of reverse bias at subcell connection—n top/p bottom interface—and a better tunnel recombination junction contributed to the improvement in the fill factor (FF). Furthermore, the quantum efficiency (QE) results also have demonstrated intermediate-reflector function of the n μc-SiO:H films.